Musical-anthropological measuring aesthetic emotions - Nadia Voronovа; Victoria Kuzmenko (Cхід, 2016)
The article actualizes the problem of the anthropological dimensions of music art on the basis of the influence of aesthetic emotions. The basis adopted three main provisions. First, the essence of the Genesis sound and emotional complexes appears in their emotional interpretation. We investigated the emotional influence of music on people in the history of aesthetic thought. Provided that the original essence of music is the history of human consciousness and subconsciousness. The leading concept in the anthropology of music, there are phenomena that are inherent as a deep structure in the development of European culture. Music expresses the consciousness on the physical, mental and spiritual levels. Culture as one of the highest forms of social organization of human consciousness is forced to structure his consciousness through the external form, including through art. This avoids a state of isolation, an inability to develop.